Critical Terrains French and British Orientalisms - Lowe, Lisa (Cornell University Press, 2018)
Examining and historicizing the concept of "otherness" in both literature and criticism, Lisa Lowe explores representations of non-European cultures in British and French writings from the eighteenth through the twentieth century. Lowe traces the intersections of culture, class, and sexuality in Lady Mary Wortley Montagu's Turkish Embassy Letters and Montesquieu's Lettres persanes and discusses tropes of orientalism, racialism, and romanticism in Flaubert. She then turns to debates in Anglo-American and Indian criticism on Forster's Passage to India and on the utopian projection of China in the poststructuralist theories of Julia Kristeva and Roland Barthes and in the journal Tel Quel.